Problem solving ability: The impact of student worksheets based on problem-based learning models on set material in junior high school - Rani, Thitra Padma; Sutiarso, Sugeng (Desimal: Jurnal Matematika, 2023)
The problem in this study is related to the less optimal ability to solve students' mathematical problems. Therefore, the purpose of this study was to find out and analyze the average difference in the ability to solve mathematical problems between students who apply the PBL model assisted by worksheets and those who apply the conventional learning model at one of the junior high schools in Tulang Bawang district. This study uses a quasi-experimental method. Samples were taken using the Cluster Random Sampling technique with a lottery procedure. The instrument in this study was an essay test. Hypothesis testing using t-test: prior to testing the hypothesis, prerequisite tests were first carried out, namely the normality test and homogeneity test. From the results of the hypothesis testing, it can be concluded that the application of the PBL model with the help of student worksheets can improve students' mathematical problem-solving abilities. Worksheets made with PBL syntax can facilitate and improve students' problem-solving abilities. This can be seen in the increase in the average value of the class that applies the PBL model